Graphical representations of message exchanges into web service-based applications - Pegoraro, René [UNESP] (2008)
Web service-based application is an architectural style, where a collection of Web services communicate to each other to execute processes. With the popularity increase of Web service-based applications and since messages exchanged inside of this applications can be complex, we need tools to simplify the understanding of interrelationship among Web services. This work present a description of a graphical representation of Web service-based applications and the mechanisms inserted among Web service requesters and providers to catch information to represent an application. The major contribution of this paper is to discus and use HTTP and SOAP information to show a graphical representation similar to a UML sequence diagram of Web service-based applications.